Developing an appropriate land use methodology to promote spatially just, formal retail areas in developing countries: The case of the City of Cape Town, South Africa. (July 2016) - Denoon-Stevens, Stuart Paul
Highlights: This paper explores the idea of spatial justice within the City of Cape Town land use scheme. It argues for mandatory inclusion of informal traders & micro-enterprises in formal retail areas. It also argues for using the land use scheme to mandate the creation of pedestrian friendly areas. To mitigate the financial impact on developers, it lastly proposes a property tax abatement. Abstract: South African scholars have increasingly recognized that the prevailing management system for land use is one not relevant to the current spatial needs of the country's settlements. These include, in particular, the need to create sustainable, spatially just and resilient settlements and to develop land in a manner that promotes efficient urban development. The debate in the South African literature on land use management has, with a few notable exceptions, yet to venture into the specific mechanics of how to fix this system, ways the system can be used to create a spatially just urban form, or its applicability in formal retail areas. This paper addresses these questions within the context of formal retail areas and the zoning category that these are typically found in, namely that of the General Business zone. This paper initially investigates the current exclusionary nature of formal retail areas in the context of South Africa and within Cape Town and how this is linked to the more macro patterns of spatial exclusion within Cape Town. It is argued that within the context of Cape Town there is a need to focus on both commercial, particularly formal retail, as well as residential, areas with regard to the project of creating a more spatially just city. It is subsequently demonstrated, firstly, how zoning scheme provisions could be used as a mechanism to address these patterns of exclusion in formal retail areas, specifically exploring provisions that would encourage inclusion of informal and microenterprises within shopping malls. Secondly, it is demonstrated how provisions can be included that create a safer and more inviting environment for public transport users and poorer employees and consumers, in formal retail areas. The contribution of this paper is to initiate a long overdue conversation regarding the relationship between land use management and social justice within a developing world context, and in formal retail areas, and aims to set out ways in which land use management can be made more relevant; both for South African cities and cities in other developing countries.